RELIGIOUS FACTOR COVARIATE ON SUBSTANCE ABUSE AMONG UNIVERSITY STUDENTS: A COMPARATIVEANALYSIS BETWEEN GENDER - Khaizir hj Ismail (Program Pascasarjana Universitas Islam Negeri Sultan Syarif Kasim Riau, 2014)
This research examines the issue of substance abuse among first year students of National University of Malaysia. A total of 1000 students aged 18 until 23 years old comprising 271 male and 729 female students were involved in the study. To measure the level of tendency to abusedrugs, SASSI-2(Substance Abuse Subtle Screening), a psychology measuring instrument was used, containing 8 scales which are Family friends risk, Attitude, symptom, Obvious attributes, subtle attributes, Defensiveness, Supplemental addiction measure dan Correctional. Meanwhile, religiosity instrument is used for the purpose of measuring the practice of religious duties. From the independent sample t-test and Multivariate Analysis of Variance (MANOVA) conducted, differences in the pattern of substanceabuseamong male and female students were identified. The result of multivariate analisis covariate test (MANCOVA)showed that religiosity can be a determining factor in the tendency of students to be involved in substance abuse